Factors of related to work motivation of health officers during Covid-19 pandemic at UPT RSUD Tenriawaru, Bone Regency - Hermadani, Hermadani; Rusmin, Muhammad; Nildawati, Nildawati (Unified Health Critical Research, 2025)
The increase in the number of Covid-19 cases occurred quite quickly which had a very broad impact on the world of work which caused economic and health problems to be disrupted. This study aims to determine the factors related to the motivation of health workers at UPT RSUD Tenriawaru Kab. Bone This type of research is quantitative research using a cross sectional approach. The population in this study were all health workers who handled Covid-19 at the UPT RSUD Tenriawaru Kab. Bone numbered 51 people with a total sampling technique of sampling. The results showed that there was a significant relationship between compensation (p-value=0.004), responsibility (p-value=0.048), rewards (p-value=0.001) and interpersonal relationships (p-value=0.006) with the motivation of health workers at UPT. Tenriawaru Hospital, Kab. Bone. There was no relationship between working conditions (p-value=0.664) and with the motivation of health workers at UPT RSUD Tenriawaru Kab. Bones. It is hoped that the hospital will pay attention to compensation, working conditions, responsibilities, awards and interpersonal relationships so that health workers can work optimally, especially during the Covid-19 pandemic.